Review of Rhabdiasidae (Nematoda) from the Holarctic - Kuzmin, Yuriy (Zootaxa, 2013)
The review deals with the species of Rhabdiasidae Railliet, 1915 occurring in the Holarctic. Descriptions of 26 species from the genera Rhabdias Stiles et Hassal, 1905 (21 species), Entomelas Travassos, 1930 (4 species), and KurolonemaSzczerbak et Sharpilo, 1969 (1 species) are presented. Additionally, 5 species of Rhabdias are listed as species inquirenda, and 4 species are included into the review, since they have been reported close to south-eastern border of Palaearctic (the exact distribution is unknown). Keys to the Holarctic species and diagnoses of the genera are provided. An overview of the information on the biology, morphology and taxonomy of Rhabdiasidae is also presented, as well as the host-parasite list of Holarctic Rhabdiasidae.